(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2023)
The need to harness the vast energy resources of the oceans has led to a significant increase in the design, testing and deployment of novel technologies for Marine Renewable Energy (MRE). However, growth in this area has been slowed in part by several non-technological challenges, among them the ability to gain permissions to test and deploy installations. These consenting processes are often characterised by long bureaucratic procedures (with many authorities involved) and excessive environmental impact assessment studies, resulting in delays and additional costs to developers. One option which may help to release this block is to adopt a Risk-Based Approach (RBA) to energy consenting, whereby an assessment of risk is used in the decision-making process. The EU-funded SafeWAVE project (www.safewave-project.eu) has focussed on this possibility in France and Ireland, building on the work of an earlier EU-funded project, WESE (https://www.researchgate.net/project/Wave-Energy-in-the-Southern-Europe-WESE), in which similar work was undertaken in Spain and Portugal. Here we present some of the findings from these projects, in particular the process to work towards a set of guidance for the use of RBAs in MRE consenting processes. RBAs have already been used in the context of Marine Spatial Planning and Ecosystem-Based Management and have been found to be useful for interpretation of data from experts, indicators and ecosystem models. Indeed, a number of RBAs have also been developed that are appropriate for Marine Renewable Energy (MRE) consenting processes. A thorough review was undertaken of several recognised RBAs and common components were identified across five of the most useful and relevant of these. From these common components, a ‘stepwise process’ was formulated, specifically designed to be embedded into MRE consenting systems. This stepwise process has been constructed such that it can be presented to regulatory stakeholders in France and Ireland with a view to determining the feasibility of its implementation. Ultimately the outcome of these discussions will form the basis for the development of a guidance document on risk based, adaptive management consenting processes with recommendations on how the process can be taken forward and utilised by regulators, planners and developers. While the development of a prescriptive procedure is not feasible (due to the varying nature of the MRE installations devices themselves as well as differing environmental conditions and impacts where devices are deployed), there is scope for providing guidance to assist regulators in taking a robust and holistic risk-based approach. Such a set of guidelines could facilitate a broader understanding and thus the wider use of RBAs, which in turn has the potential to remove one significant barrier to progress in the field.